2010
DOI: 10.1074/jbc.m109.041046
|View full text |Cite
|
Sign up to set email alerts
|

The TSG-6/HC2-mediated Transfer Is a Dynamic Process Shuffling Heavy Chains between Glycosaminoglycans

Abstract: The heavy chain (HC) subunits of the bikunin proteins are covalently attached to a single chondroitin sulfate (CS) chain originating from bikunin and can be transferred to different hyaluronan (HA) molecules by TSG-6/HC2. In the present study, we demonstrate that HCs transferred to HA may function as HC donors in subsequent transfer reactions, and we show that the CS of bikunin may serve as an HC acceptor, analogous to HA. Our data suggest that TSG-6/HC2 link HCs randomly on the CS chain of bikunin, in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Proteoglycanenriched urine and plasma samples analyzed in this study were found to contain the same level of bikunin. I␣I and HC-bikunin in plasma were found to contain HC1 and HC2 that could not be completely separated by chondroitinase ABC digestion, a phenomenon that has been reported previously (4,18,37,40,41). The absence of un-and 6-sulfated CS linkage region structures attached to bikunin has been reported previously (9) and was confirmed in this study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Proteoglycanenriched urine and plasma samples analyzed in this study were found to contain the same level of bikunin. I␣I and HC-bikunin in plasma were found to contain HC1 and HC2 that could not be completely separated by chondroitinase ABC digestion, a phenomenon that has been reported previously (4,18,37,40,41). The absence of un-and 6-sulfated CS linkage region structures attached to bikunin has been reported previously (9) and was confirmed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Experiments were performed in the presence or absence of TSG-6 and confirmed that it is required for the formation of HA⅐HC through intermediate TSG-6⅐HC complexes (4,37,48,49). The in vitro assays utilized in this study to monitor HC⅐HA formation used excess purified recombinant TSG-6 to obtain maximal substitution of HA in each of the plasma fractions (18). The Western blot assay analyzed the M r reactivity of bikunin, HC2, and TSG-6 as both HC2 and TSG-6 have been reported to be necessary for the trans-esterification reaction to occur (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction with TSG-6 Does Not Affect Complement Inhibition by I␣I-TSG-6 was reported to covalently bind I␣I at an equimolar ratio and transfer its heavy chains to hyaluronan moieties (10). As the complement inhibitory activity of I␣I is localized to the heavy chains, we tested if intramolecular rearrangements caused by TSG-6 impair the ability of I␣I to downregulate complement.…”
Section: I␣i Does Not Inhibit C1s But Prevents Formation Of the Classmentioning
confidence: 99%
“…Thus, bikunin and I␣I are implicated in such processes as oocyte maturation and ovulation (6), protection from sepsis (7), stabilization of hyaluronan coat on cell surfaces (8), and protection of hyaluronan-containing extracellular matrix components from degradation in arthritic synovial fluid (9). Concerning the interaction with hyaluronan, TNF-stimulated gene 6 protein (TSG-6) plays an essential role as it supports two subsequent transesterification reactions: first it binds covalently HC1 or HC2 of I␣I and then in such a complex transfers them to hyaluronan moieties, where heavy chains become conjugated and free TSG-6 released (10,11). Elevated levels of covalent HC-hyaluronan complexes were found in sera (12) as well as synovial fluids (13) of rheumatoid arthritis (RA) patients.…”
mentioning
confidence: 99%